(untitled) (Fiep Bulletin - online, 2014)
With the increase of the feminine participation in the practice of sports, they noticed their benefits, such as physiologic, psychological and social effects. The practice of sports of high intensity results in health problems, as evidenced in competition athletes that present high incidence of menstrual irregularities, as athletic amenorrhea, this is the absence of menstrual cycles characterized by low levels of estrogen in circulation. It was aimed to approach the physiopathological aspects, etiological and nutritional of the treatment of the athletic amenorrhea, likewise providing a better income of the training. Several factors are associated to the athletic amenorrhea and the most frequent are: the low caloric consumption, the intensity of the training, the retard of the beginning of the menstrual function, the disturbances of the ingestion, the stress, the low corporal weight and the low percentile of corporal fat. The prevalence of this menstrual dysfunction is larger among the women athletes’ group when compared to the general population. The psychological and physiologic stress induced by the competition and the intense physical training can increase the production of androgenic adrenals and to modify the metabolic clearance of estrogens, exercising an important paper in the etiology of the amenorrhea. The ingestion of calcium must be monitored once the appropriate consumption is extremely important for athletes in growth, because it reduces the stress fractures and the risk of osteoporosis development, being important for female athletes that present primary amenorrhea, which is associated to a smaller bone density. The alimentary disturbances among the sportspeople also appear close to the other types of alimentary problems, related to the maintenance of the corporal weight. It is necessary to maintain the appropriate corporal level, because it influences directly to this menstrual dysfunction. It is of extreme importance the attendance at the dietary nutritional planning in the treatment and in the prevention of the athletic amenorrhea, with the purpose of providing an improvement in the female athletes’ income.